If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 12x = 16x + -55 Reorder the terms: 1 + 12x = -55 + 16x Solving 1 + 12x = -55 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 1 + 12x + -16x = -55 + 16x + -16x Combine like terms: 12x + -16x = -4x 1 + -4x = -55 + 16x + -16x Combine like terms: 16x + -16x = 0 1 + -4x = -55 + 0 1 + -4x = -55 Add '-1' to each side of the equation. 1 + -1 + -4x = -55 + -1 Combine like terms: 1 + -1 = 0 0 + -4x = -55 + -1 -4x = -55 + -1 Combine like terms: -55 + -1 = -56 -4x = -56 Divide each side by '-4'. x = 14 Simplifying x = 14
| -3-5x+20+2x=5 | | 10x+5y=13 | | 6x+7=4x+12 | | 3t+4=t+14 | | 4x-6=-2 | | 200-6x=6x+20 | | -55-4x=5-10x | | -55-4=5-10x | | 5x+7-8x+6x=13 | | 8a-10+a+2-4a=16 | | 8a-10+a+2-4a=17 | | x^2+169=0 | | 7y-8=13 | | 6x^3+13x^2-38x+12= | | 6x^3+12x^2-38x+12= | | 3p^2-19+28=0 | | 2k^2-13k+11=0 | | 5n^2+26n+5=0 | | m^2+m-56=0 | | a^2-9a+20=0 | | p^2+18p+81=0 | | d^2+10d+24=0 | | 4x-2(6)=4 | | 3x=x-20 | | 5(4-2y)=26 | | 4x+22=26 | | 5(9.5)+y=26 | | 3(2x+1)=18x | | B=rt+r | | 4x+2(-5+26)=4 | | 7(a+2)=2(2a-1) | | 8x-(2x+4)=32 |